Preliminary study on the development of formulated ready-to-drink calamansi (Citrus microcarpa Bunge ) juice - Barros , Lugene Mae R.
Formulated ready-to-drink calamansi juice were prepared using four different treatments namely: A1 (using muscovado and brown sugar stored under room temperature), A2 (using muscovado and brown sugar stored under chilled temperature), B1 (using brown sugar stored under room temperature), B2 (using brown sugar and stored under chilled temperature).